Covalent Attachment of Enzymes to Paper Fibers for Paper-Based Analytical Devices - Böhm, Alexander; Trosien, Simon; Avrutina, Olga; Kolmar, Harald; Biesalski, Markus (Frontiers in Chemistry, 2018)
Due to its unique material properties, paper offers many practical advantages as a viable platform for sensing devices. In view of paper-based microfluidic biosensing applications, the covalent immobilization of enzymes with preserved functional activity is highly desirable and ultimately challenging. In the present manuscript, we report an efficient approach to achieving the covalent attachment of certain enzymes on paper fibers via a surface-bound network of hydrophilic polymers bearing protein-modifiable sites. This tailor-made macromolecular system consisting of polar, highly swellable copolymers is anchored to the paper exterior upon light-induced crosslinking of engineered benzophenone motifs. On the other hand, this framework contains active esters that can be efficiently modified by the nucleophiles of biomolecules. This strategy allowed the covalent immobilization of glucose oxidase and horseradish peroxidase onto cotton linters without sacrificing their bioactivities and performance upon surface binding. As a proof-of-concept application, a microfluidic chromatic paper-based glucose sensor was developed and achieved successful glucose detection in a simple yet efficient cascade reaction.